2018
DOI: 10.1042/bsr20181822
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin inhibits proliferation and induces autophagy in human neuroblastoma cells

Abstract: Objective To investigate the effect of Rapamycin on proliferation and autophagy in human neuroblastoma (NB) cell lines and to elucidate the possible mechanism. Methods NB cells were treated with different concentrations of Rapamycin. Cell counting kit-8 (CCK-8) was used to measure proliferation, and flow cytometry (FCM) was used to analyze the cell cycle. EM was used to observe cell morphological changes. Western blotting (WB) was performed to detect the expression of Beclin-1, LC3-I/II, P62, mammalian target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 25 publications
1
49
0
Order By: Relevance
“…Recent research revealed induction of autophagy by cystatin c plays a protective role in murine primary cortical neurons and neuronal cell lines under conditions of neuronal challenge by inducing autophagy via the inhibition of mammalian target of rapamycin (mTOR) [38] and mTOR forms the catalytic core of at least two functionally distinct complexes, mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2) [8]. In the present study, we induced autophagy using rapamycin, a special prophylactic for mTOR that inhibits mTOR activity [39] thereby inducing autophagy [40]. Indeed, rapamycin preferentially inhibits mTORC1 by interfering with complex assembly and thereby suppresses mTORC1 downstream targets, including ribosomal S6 protein kinase 1 (S6K1), eukaryotic initiation factor 4E-binding protein 1 (4EBP1), and UNC-51-like kinases (ULKs).…”
Section: Discussionmentioning
confidence: 92%
“…Recent research revealed induction of autophagy by cystatin c plays a protective role in murine primary cortical neurons and neuronal cell lines under conditions of neuronal challenge by inducing autophagy via the inhibition of mammalian target of rapamycin (mTOR) [38] and mTOR forms the catalytic core of at least two functionally distinct complexes, mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2) [8]. In the present study, we induced autophagy using rapamycin, a special prophylactic for mTOR that inhibits mTOR activity [39] thereby inducing autophagy [40]. Indeed, rapamycin preferentially inhibits mTORC1 by interfering with complex assembly and thereby suppresses mTORC1 downstream targets, including ribosomal S6 protein kinase 1 (S6K1), eukaryotic initiation factor 4E-binding protein 1 (4EBP1), and UNC-51-like kinases (ULKs).…”
Section: Discussionmentioning
confidence: 92%
“…For example, rapamycin is a selective inhibitor of mTORC1 and causes activation of autophagy (209). In several studies, rapamycin has been demonstrated to suppress cancer proliferation and induce autophagic cell death in different cancer models, such as neuroblastoma, osteosarcoma, and sarcoma (210)(211)(212). Rapamycin analogs (rapalogs), such as temsirolimus and everolimus, also inhibit the mTOR pathway in renal cancer and breast cancer, among others (213,214).…”
Section: Autophagy As a Target For Therapeutic Purposes: Inhibition Omentioning
confidence: 99%
“…Furthermore, the induction of autophagy associated to mTOR inhibition may mediate some effects on tumor development [ 95 ]. Rapamycin has been shown to inhibit proliferation and induce autophagic cell death in murine sarcoma, neuroblastoma, lung cancer and osteosarcoma [ 96 , 97 , 98 , 99 ]. In addition, Everolimus (or RAD001), a rapamycin analogue, was approved by FDA for use in different types of tumors, including advanced renal cell carcinoma, advanced pancreatic neuroendocrine tumors, renal angiomyolipoma and HER2-negative breast cancer.…”
Section: Autophagy In Cell Response To Cancer Treatmentmentioning
confidence: 99%